Hubungan Antara Kecerdasan Emosi dan Penyesuaian Diri pada Mahasiswa Baru di Universitas Aisyah Pringsewu Tahun 2023 - Vivi Dwi Silfia; Rima Wilantika (Jurnal Psikologi, 2023)
This study aims to determine the correlation between emotional intelligence and self-adjustment in new students at Aisyah University of Pringsewu. The population in this study were new students at the Aisyah University of Pringsewu. There were 94 research subjects who came from various study programs at Aisyah University of Pringsewu. Data collection used the emotional intelligence scale (22 items with correlation coefficients ranging from 0.283-0.881; α = 0.951) and self-adjustment scales (38 items with correlation coefficients ranging from 0.255-0.696; α = 0.909). The effective contribution of emotional intelligence and self-adjustment is 39.56%, according to the coefficient of determination. A positive correlation between emotional intelligence and adjustment in new students was found through data analysis using the Product Moment correlation (r = 0.629; p = 0.000). This demonstrates a positive correlation between emotional intelligence and self-adjustment, and a negative correlation between emotional intelligence and self-adjustment.